1980
DOI: 10.2527/jas1980.512294x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Dietary Additions of Alfalfa and Tallow on Sow Reproductive Performance

Abstract: SummaryEighty-eight crossbred sows were used to evaluate the effects of including sun-cured alfalfa in gestation diets and tallow in lactation diets on reproductive performance for three successive reproductive cycles. Two pelleted gestation diets were fed: (1) no alfalfa and (2) 50% alfalfa. Both diets were fed at the rate of 6,000 kcal of ME/head/day for the first 90 days of gestation. Two lactation diets were fed, one containing no added tallow and the other 8% stabilized tallow. Lactation diets were initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…Reports on changes in daily nutrient intake as a result of increased dietary energy have been variable. Pollman et al (1980) reported decreased feed intakes, but similar ME intakes, when sows were fed diets with or without 8% added tallow. Sows fed highenergy diets with 1ysine:energy ratios maintained at the level of the control diets have been reported to increase feed intake by 3% and increase energy intake by 14% (O'Grady et al, 1985).…”
Section: Effect Of Seasonmentioning
confidence: 79%
“…Reports on changes in daily nutrient intake as a result of increased dietary energy have been variable. Pollman et al (1980) reported decreased feed intakes, but similar ME intakes, when sows were fed diets with or without 8% added tallow. Sows fed highenergy diets with 1ysine:energy ratios maintained at the level of the control diets have been reported to increase feed intake by 3% and increase energy intake by 14% (O'Grady et al, 1985).…”
Section: Effect Of Seasonmentioning
confidence: 79%
“…This may reflect an increase in the caloric density of the tallow-supplemented diet. Other researchers have reported a reduction in daily feed intake due to the addition of fat to the diet (Cast et al, 1977;Boyd et ai., 1978;Allee and Salava, 1978;Pollmann et al, 1980). Survival to 21 d did not differ significantly between pigs from sows receiving tallow (94.0%) and those from sows receiving the control diet (92.5%).…”
Section: R~ults and Discuuionmentioning
confidence: 82%
“…Microbial degradation of fiber in the cecum and colon of pigs may generate up to 30% of the animal's energy requirement (Rerat et al, 1987). This figure may even be higher for adult animals because sows can maintain normal reproductive performance when fed diets containing 96% to 100% alfalfa meal (Danielson and Noonan, 1975;Pollman et al, 1981;Calvert et al, 1985), and the numbers of cellulolytic bacteria in fecal samples of adult pigs are larger than those in growing pigs (Varel and Pond, Z Received April 27, 1987. Accepted October 20, 1987.…”
Section: Introductionmentioning
confidence: 99%